Association Between Polymorphisms in Gastric Cancer Related Genes and Risk of Gastric Cancer: A Case-Control Study - Pu, Yan; Wen, Xu; Jia, Zhangjun; Xie, Yu; Luan, Changxing; Yu, Youjia; Chen, Feng; Chen, Peng; Li, Ding; Sun, Yan; Zhao, Jian; Lv, Haiqin (Frontiers in Molecular Biosciences, 2021)
Gastric cancer has the second highest incidence among all the malignancies in China, just below lung cancer. Gastric cancer is likewise one of the main sources of cancer related passings. Gastric cancer therefore remains a huge threat to human health. The primary reason is absence of high sensitivity and specificity for early detection while the pathogenesis of GC is stayed muddled. During the last few decades, a lot of GC related genes have been identified. To find candidate GC related variant in these GC related genes, we conducted this case-control study. 29 tagSNPs located in 7 GC related genes were included. 228 gastric cancer patients and 299 healthy controls were enrolled. Significant differences were found between the genotype frequencies of EFNA1 rs4971066 polymorphism between gastric cancer patients and healthy controls. The result indicated that ephrin-A1 tagSNP rs4971066 GT/TT genotypes was significantly associated with reduced susceptibility of gastric cancer development.